The application of IQWorks image analysis software to quality assurance in MR imaging. (7th April 2016) - Fazakerley, J; Brunt, J N H; Graham, J; Reilly, A; Moores, B M
Abstract: Recent developments have made available free software tools that would expedite local quality assurance (QA) in magnetic resonance imaging (MRI), incorporating established methodology. IQWorks is a software package for digital Imaging and communication in medicine image analysis, which was found to have highly appropriate functionality. Key advantages are provided by the definition of an analysis process via an 'analysis tree', which facilitates user-implementation (without the need for further programming) of automated or partially automated analysis schemes incorporating testing methodology. Aspects of the analysis tree include automated region of interest positioning relative to the position of a detected edge, and production of results as PDF reports. In this study analysis trees were built to analyse the Eurospin test objects in order to assess signal to noise ratio, uniformity, ghosting, slice width, geometric linearity and spatial resolution. We aimed to examine the robustness and general applicability of IQWorks for MRI QA, by obtaining results using images from multiple scanners (various models) in routine use, and compared with results obtained from propriety manufacturers' software and other image analysis software. The use of analysis trees in IQWorks was found to provide automated implementation of specified analysis protocols without reliance on manual placement of sampling regions of interest. Results obtained were highly congruent with those obtained using scanner console analysis tools. We conclude that IQWorks expedites development of local MRI QA incorporating nationally established methodology, and facilitates the implementation of QA procedures by staff without appropriate programming expertise. The analysis tree methodology would expedite implementation of revised protocols in new guidance documents.